Enalapril effects on renal function and ACE gene polymorphism in hypertensive nephropathy - K. Y. Zholdoshov; R. R. Kaliev; A. A. Aldashev; A. B. Budaychieva; Ch. R. Sultakeeva; V. M. Ayylchieva (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the effects of enalapril on 24-hour proteinuria, renal function, intra-renal hemodynamics and survival, in regard to ACE gene polymorphism I/D, among patients with essential arterial hypertension (EAH). Material and methods. In total, 83 EAH patients were examined (mean age 41,48±1,25 years) as the main group (MG). The control group (CG) included 30 healthy people and was comparable to MG by gender and sex distribution. All participants underwent general clinical examination, assessment of 24-hour proteinuria and glomerular filtration rate (GFR), electrocardiography, echocardiography, renal ultrasound and renal vessel triplex scanning. ACE gene polymorphism was assessed by polymerase chain reaction method. Results. In EAH patients, D allele of ACE gene was associated, despite ACE inhibitor therapy during 4 years of the follow-up, with development of hypertensive nephropathy (HN), with an increase in 24-hour proteinuria from 276,67±112,13 to 836,50±294,50 mg/d, especially in individuals with DD genotype. The same group of patients developed renal failure: in 8 years, GFR decreased to 36,78±7,59 ml/min, while in patients with I allele, renal function was intact. Ten-year survival of EAH patients with DD genotype (all individuals developed renal failure) was significantly lower than in individuals with I allele. In EAH patients with II genotype, enalapril therapy resulted in vasodilatation and decreased resistivity and pulsatility indices, while no similar changes were observed in patients with DD genotype. Conclusion. Despite ACE inhibitor therapy, EAH patients with DD genotype were characterised by increased 24-hour proteinuria, reduced GFR, increased resistivity and pulsatility indices, and worse 10-year survival, compared to patients with I allele.